Reliable and highly specific techniques for the detection of Brucella spp. antibodies in camel milk - Dhary A. Almashhadany; Hero I. Mohammed; Ahmed M. Zaki; Rawaz R. Hassan (Iraqi Journal of Veterinary Sciences, 2023)
Brucellosis is one of the most serious zoonotic diseases in human and farm animals caused by Brucella species. This study aims to: (i) estimate the current prevalence of Brucella among camels in Erbil Governorate; (ii) evaluate the milk ring test as a diagnostic tool for screening of brucellosis in camels; (iii) study the association between months and percentage of positive samples to Brucella. During the period, January - June 2021, a total of 250 raw camel milk samples (130 samples from farms and 120 from sale points) were randomly collected. The brucellosis is diagnosed using the Milk Ring Test (MRT), indirect ELISA, and bacteriological isolation of Brucella species. The prevalence of Brucella antibodies in camel milk samples is 11.6% and 10.4% according to MRT and ELISA, respectively. The overall isolation percentage of Brucella species is 8.4%. The detection rate of isolates in sale points is higher 10.0% than the isolation rate from farm 6.9%. The results also reveal that 4.6% and 5.8% of isolates are Brucella abortus; while, 5.8% and 4.2% are Brucella melitensis from the milk of farm and sale points, respectively. The highest rate of brucellosis according to MRT is observed in February 18.6%, while the lowest rate is documented in May 7.5%. We recommend using MRT for the diagnosis of Brucella spp. in routine screening of brucellosis in milk collection centers, dairy factories, and farm. Customers are also recommended to heat the milk adequately to eliminate this milk-borne pathogen before drinking milk or manufacturing processes.